Ubiquitin Receptor RPN13 Mediates the Inhibitory Interaction of Diphenyldihaloketones CLEFMA and EF24 With the 26S Proteasome - Rao, Geeta; Nkepang, Gregory; Xu, Jian; Yari, Hooman; Houson, Hailey; Teng, Chengwen; Awasthi, Vibhudutta (Frontiers in Chemistry, 2018)
The proteasome is a validated target in drug discovery for diseases associated with unusual proteasomal activity. Here we report that two diphenyldihaloketones, CLEFMA and EF24, inhibit the peptidase activity of the 26S proteasome. The objective of this study was to investigate interaction of these compounds with the proteasome and identify a putative target within the protein components of the 26S proteasome. We employed standard fluorogenic peptide-based proteasome activity assay for trypsin-like, chymotrypsin-like, and caspase-like activities of human purified 26S proteasome in cell-free conditions. GFPu-1 and HUVEC cells were used as proteasome reporter cells. Direct binding studies used purified 19S, 20S, 26S, and recombinant RPN13-Pru for interaction with biotinylated analogs of CLEFMA and EF24. The reaction mixtures were subjected to horizontal gel electrophoresis, streptavidin-blotting, pull-down assays, and immunoblotting. The identity of the interacting protein was determined by 2D gel electrophoresis and LC-MS/MS. Drug affinity responsive target stability technique was utilized to examine if CLEFMA binding confers protection to RPN13 against thermolysin-catalyzed proteolysis. We found that trypsin-and chymotrypsin-like activities of the 26S proteasome were reduced significantly by both compounds. The compounds also reduced the proteolytic activity in GFPu-1 and HUVEC cells, resulting in accumulation of ubiquitinated proteins without affecting the autophagy process. From direct binding assays a 43 kDa protein in the 26S proteasome was found to be the interacting partner. This protein was identified by tandem mass spectroscopy as regulatory particle subunit 13 (RPN13), a ubiquitin receptor in the 19S regulatory particle. Furthermore, binding of CLEFMA to RPN13 did not protect latter from thermolysin-mediated proteolysis. Together, this study showed diphenyldihaloketones as potential proteasome inhibitors for treatment of diseases with perturbed proteasome function. The results also unraveled RPN13 as a unique target of CLEFMA and EF24. As a result, these compounds inhibit both trypsin-like and chymotrypsin-like proteasome activities.